1983
DOI: 10.1021/jf00118a007
|View full text |Cite
|
Sign up to set email alerts
|

Fate of ethion in canals draining a Florida citrus grove

Abstract: 6-month incubation (Table 111). In whole grain of both treatments, malathion monocarboxylic acid was the most prevalent degradation product, followed by an unknown compound. The dockage fraction, however, contained larger quantities of the unknown compound than malathion monocarboxylic acid. Both treatments contained smaller amounts of malathion and larger amounts of the degradation products after 6 months than after 2 months. Malaoxon was not found in the grain. The unknown compound did not correspond to mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In this case, flask sterility was confirmed through microscopic examination and plating on nutrient agar. Similarly, Dierberger and Pfeuffer have reported that the half‐life of Ethion in buffered (pH 7) distilled water at 30 °C is 20.8 weeks [9]. Thus, the increase in OD660 was not due to infection or hydrolysis of the Ethion.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In this case, flask sterility was confirmed through microscopic examination and plating on nutrient agar. Similarly, Dierberger and Pfeuffer have reported that the half‐life of Ethion in buffered (pH 7) distilled water at 30 °C is 20.8 weeks [9]. Thus, the increase in OD660 was not due to infection or hydrolysis of the Ethion.…”
Section: Resultsmentioning
confidence: 81%
“…The lack of these components in Ethion may support its significantly faster microbial degradation. The abiotic hydrolytic degradation products of Ethion; Ethion Monoxon, Ethion Dioxon, O,O ‐diethylthiophosphate and Thio‐formaldehyde were not observed using GC–MS [9,19]. Their absence may be due to a number of factors, however it seems most likely that Ethion and its degradation products were rapidly utilised for microbial growth.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation